2002
DOI: 10.1034/j.1399-302x.2002.170602.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of apigenin and tt‐farnesol on glucosyltransferase activity, biofilm viability and caries development in rats

Abstract: Propolis, a resinous hive product secreted by Apis mellifera bees, has been shown to reduce the incidence of dental caries in rats. Several compounds, mainly polyphenolics, have been identified in propolis. Apigenin and tt-farnesol demonstrated biological activity against mutans streptococci. We determined here their effects, alone or in combination, on glucosyltransferase activity, biofilm viability, and development of caries in rats. Sprague-Dawley rats were infected with Streptococcus sobrinus 6715 and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
150
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(158 citation statements)
references
References 51 publications
2
150
0
6
Order By: Relevance
“…Si embargo se conoce que el propóleo cuenta con flavones como apigenin, tt-farnesol, compuestos que presentan acción antibacteriana y anticaries. 7 En el país sólo existe el análisis de propiedades antimicrobianas realizado dentro del estudio de estandarización; 11 el cual comprobó la actividad antibacteriana contra Staphylococcus aureus, C. albicans y Asperguillus níger, por lo que esta investigación representa el primer paso para presentar los efectos antibacterianos en la cavidad oral.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Si embargo se conoce que el propóleo cuenta con flavones como apigenin, tt-farnesol, compuestos que presentan acción antibacteriana y anticaries. 7 En el país sólo existe el análisis de propiedades antimicrobianas realizado dentro del estudio de estandarización; 11 el cual comprobó la actividad antibacteriana contra Staphylococcus aureus, C. albicans y Asperguillus níger, por lo que esta investigación representa el primer paso para presentar los efectos antibacterianos en la cavidad oral.…”
Section: Resultados Y Discusiónunclassified
“…4,5 Otros autores han estudiado fracciones y componentes del Propó-leo demostrando que la fracción H-fr y los flavones (apigenin y tt-farnesol) presentan alta actividad antibacteriana y poder inhibitorio de la Glucosil transferasa (GTF) con reducción de caries dental. 6,7 Por otro lado en estudios clínicos se ha comprobado que un colutorio a base de Propóleo no presentó actividad antiplaca significativa, pero su actividad antibacteriana fue semejante a la clorhexidina, 8 asimismo una crema dental con Propóleo redujo significativamente el promedio de piezas afectadas con caries dental; 9 otro estudio determinó que el Propó-leo tiene alta concentración de calcio (Ca 2+ ) y la dureza del esmalte mostró un aumento constante en proporción directa al aumento de concentración de la solución. 10 La geografía peruana y su diversa vegetación se prestan para el desarrollo de la apicultura, al punto que está en vías de ser una industria.…”
Section: Introductionunclassified
“…10,15,16,23,32 In these studies, ethanolic extracts of propolis, or its bioactive fractions, were applied topically to the molars of rats twice a day for a period of 4 to 5 weeks. Overall, the authors observed anti-caries activity similar to that of Duraphat ® .…”
Section: Discussionmentioning
confidence: 99%
“…Topical applications of tt-farnesol (1 min exposure, twice daily) diminished the EPS content and development of single-species S. mutans biofilms on saliva-coated hydroxyapatite (sHA) surfaces, and reduced the severity of smooth-surface caries in rats [10]. However, treatment is not lethal to S. mutans biofilms in vitro, did not inhibit glucosyltransferases activity, and tt-farnesol displayed minimal effects on the viability of the oral flora populations in vivo [10,[12][13]. It is possible that tt-farnesol may cause acid sensitization and affect intracellular metabolism of S. mutans by disrupting the bacterial membrane function due to its fatty acid-like structure and lipophilic characteristics [10,12]; consistent with reduction of IPS accumulation in S. mutans biofilms treated with tt-farnesol [11,13].…”
mentioning
confidence: 99%
“…However, treatment is not lethal to S. mutans biofilms in vitro, did not inhibit glucosyltransferases activity, and tt-farnesol displayed minimal effects on the viability of the oral flora populations in vivo [10,[12][13]. It is possible that tt-farnesol may cause acid sensitization and affect intracellular metabolism of S. mutans by disrupting the bacterial membrane function due to its fatty acid-like structure and lipophilic characteristics [10,12]; consistent with reduction of IPS accumulation in S. mutans biofilms treated with tt-farnesol [11,13]. We hypothesize that tt-farnesol can directly affect S. mutans physiology by damaging the cell-membrane, and thereby disrupt its ability to compete and become dominant in a mixed-species biofilm environment.…”
mentioning
confidence: 99%